Aggregation kinetics of UV-aged soot nanoparticles in wet environments: Effects of irradiation time and background solution chemistry. (1st August 2021) - Duan, Zhihui; Wang, Ping; Yu, Guangwei; Liang, Miaoting; Dong, Jiawei; Su, Jiana; Huang, Weilin; Li, Yongtao; Zhang, Aiqian; Chen, Chengyu
Highlights: Irradiation by UV for > 1 d greatly promoted aggregation of SNPs in wet environments. The aggregation-enhancement effect was stronger at low salt concentration and pH > 4. UV-aging reduced electrical repulsion and enhanced van der waals attraction of SNPs. Both fresh and aged SNPs exhibited aggregation kinetics predictable from DLVO theory. Enhanced SNP aggregation was stabilized by macromolecules with BSA > HA > ALG > FA. Abstract: Soot nanoparticles (SNPs) undergo aging processes in aqueous systems, altering their physicochemical properties and affecting their fate and transport. This study investigated the aging effects via ultraviolet irradiation on aggregation kinetics of SNPs in water. The results showed that, compared to fresh SNPs, those irradiated for 1 day aggregated more easily in NaCl and CaCl2 solutions, with reduction of critical coagulation concentrations by 72% and 40%, respectively. Similar phenomena were found in additional six electrolyte solutions, and SNPs irradiated for > 3 days had no measurable difference in aggregation rate. The aggregation-enhancement of irradiated SNPs was more prominent at low electrolyte concentrations and pH > 4. However, in the presence of macromolecules, irradiated SNPs could be stabilized against aggregation via steric hindrance with strength of bovine serum albumin > humic acid > alginate > fulvic acid, whereas alginate further destabilized aged SNPs via calcium bridging. The fitted Hamaker constant increased from 7.8 × 10 −20 (fresh) to 1.2 × 10 −19  J (7-day irradiated), suggesting that decarboxylation during irradiation may weaken electrical repulsion and enhance van der Waals attraction, promoting aggregation. These results demonstrated the vital role of UV-induced aging in fate and transport of SNPs in wet environments. Graphical abstract: Image, graphical abstract